2019
DOI: 10.1038/s41598-019-44744-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic comparisons of fall armyworm populations from 11 countries spanning sub-Saharan Africa provide insights into strain composition and migratory behaviors

Abstract: The recent discovery of fall armyworm ( Spodoptera frugiperda , J.E. Smith) in Africa presents a significant threat to that continent’s food security. The species exhibits several traits in the Western Hemisphere that if transferred to Africa would significantly complicate control efforts. These include a broad host range, long-distance migratory behavior, and resistance to multiple pesticides that varies by regional population. Therefore, determining which fall armyworm subpopulations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
124
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(140 citation statements)
references
References 48 publications
14
124
2
Order By: Relevance
“…There are three strain-specific sites (E4165, E4168 and E4183) in the fourth exon of the Tpi gene that can identify the C strain from the R strain for Western Hemisphere populations 57 . Especially, the E4183 is an effective diagnostic marker for Tpi gene to define the C or R strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three strain-specific sites (E4165, E4168 and E4183) in the fourth exon of the Tpi gene that can identify the C strain from the R strain for Western Hemisphere populations 57 . Especially, the E4183 is an effective diagnostic marker for Tpi gene to define the C or R strain.…”
Section: Resultsmentioning
confidence: 99%
“…We identified the Tpi gene fragments from four FAWs, including two from Yunnan province (sequences were retrieved from the whole genome sequencing data) and two from Guangdong province (sequences were retrieved from the RNA-seq data). Eight sites (TpiE4-129, TpiE4-144, TpiE4-165, TpiE4-168, TpiE4-180, TpiE4-183, TpiE4-192, TpiE4-198) in the fourth exon of the Tpi gene were used for determining the strains and a possible source of the invaded FAW 57 . The fourth intron of the Tpi gene 57 was used for constructing the phylogenetic tree using the PhyML (v3.0) 58 software with the Maximum-Likelihood methods to assist in identifying the strains.…”
Section: Methodsmentioning
confidence: 99%
“…Because of their hybridization, identification based on the maternally-inherited mitochondrial genotype is inaccurate and the insertion of two C-strain mitochondrial fragments in this study further confirms this inaccuracy. Therefore, it is not possible to accurately infer fall armyworm strain status based on the complete mitochondrial genome or the single COI mitochondrial gene, as suggested previously [40][41] . The Tpi gene, located in the nuclear genome, is more suitable for strain identification and 10 SNPs in this gene can distinguish between R-or C-strains fall armyworm in the Americas 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the molecular identification of the two strains of fall armyworm is dependent on which markers are used [35][36][37] . The early molecular markers based on mitochondrial Cytochrome Oxidase Subunit I (COI) and Z-chromosome-linked Triosephosphate isomerase (Tpi) genes failed to accurately assign strain identification [38][39][40][41] . The dominant population of fall armyworm invading Africa and Asia were speculated to be hybrid populations of the female R-strain and male C-strain, based on these two molecular markers 42 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation